2021
DOI: 10.1101/2021.09.06.459053
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Smoothness discriminates physical from motor imagery practice of arm reaching movements

Abstract: Physical practice (PP) and motor imagery practice (MP) lead to the execution of fast and accurate arm movements. However, there is currently no information about the influence of MP on movement smoothness, nor about which performance parameters best discriminate these practices. In the current study, we assessed motor performances with an arm pointing task with constrained precision before and after PP (n= 15), MP (n= 15), or no practice (n= 15). We analyzed gains between Pre- and Post-Test for five performanc… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 46 publications
(29 reference statements)
0
2
0
Order By: Relevance
“…Firstly, at a functional level, motor imagery practice seems to induce positive changes within motor planning (Gentili et al, 2010; Taube et al, 2014). Indeed, via the activation of the neural network implicated in motor planning, motor imagery training could help to refine the internal representation of the considered action by the generation of sensorimotor predictions, leading to an improvement of motor command (Kilteni et al, 2018; Dahm and Rieger, 2019; Ruffino et al, 2022). Secondly, the modulation observed at both neural (Ruffino et al, 2017) and spinal (Grosprêtre et al, 2016) levels during motor imagery seems to reinforce the sensibility and the conductivity of synapses in corticospinal pathway (Avanzino et al, 2015), notably by increasing the effectiveness between pre- and post-synaptic neurons.…”
Section: Discussionmentioning
confidence: 99%
“…Firstly, at a functional level, motor imagery practice seems to induce positive changes within motor planning (Gentili et al, 2010; Taube et al, 2014). Indeed, via the activation of the neural network implicated in motor planning, motor imagery training could help to refine the internal representation of the considered action by the generation of sensorimotor predictions, leading to an improvement of motor command (Kilteni et al, 2018; Dahm and Rieger, 2019; Ruffino et al, 2022). Secondly, the modulation observed at both neural (Ruffino et al, 2017) and spinal (Grosprêtre et al, 2016) levels during motor imagery seems to reinforce the sensibility and the conductivity of synapses in corticospinal pathway (Avanzino et al, 2015), notably by increasing the effectiveness between pre- and post-synaptic neurons.…”
Section: Discussionmentioning
confidence: 99%
“…The positive effects of PP on motor performance can be observed with different timescales, from a single practice session to several days or weeks of practice. Previous studies reported that a few minutes of practice is enough to improve motor performance on various tasks, such as pointing or sequential finger-tapping (Spampinato et al 2017;Ruffino et al 2022;Walker et al, 2003). This fast-learning process is defined as motor acquisition and is considered the first step in the development of new motor memories.…”
Section: Introductionmentioning
confidence: 99%